PENDEKATAN KOMUNIKASI PENYULUH PERTANIAN PADA PETANI JAGUNG DI DESA LANGKORONI KECAMATAN MALIGANO KABUPATEN MUNA - Muliyana Muliyana; Ima Astuty Wunawarsih; Salahuddin Salahuddin; Arfiani Arfiani (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The objective of this study is to ascertain the communication approach employed by agricultural extension workers in the formation of corn farmer groups in Langkoroni Village, Maligano District, Muna Regency. The study population consisted of six corn farmer groups, each comprising 20 farmers, for a total population of 120 individuals. The research sample was selected using the simple random method. The sample size was determined using the Slovin formula with an error rate of 10%, resulting in a sample size of 54 respondents. This research employs a quantitative data approach. The data were collected through the use of survey, interview, and recording methods with the incorporation of media in the form of questionnaires or other pertinent documentation. The object of investigation is the communication approach of agricultural extension workers, which encompasses individual approaches (personal), group approaches (group), and mass approaches (mass). In the process of data processing and analysis, the data were processed and analyzed using the class interval formula. The results demonstrated that the communication approach of agricultural extension in developing corn farmer groups in Langkoroni Village, Maligano Subdistrict, Muna Regency has been effectively implemented by the agricultural extension officers responsible for the area (Langkoroni Village). The agricultural extension communication approach encompasses individual, group, and mass approaches, each of which has been executed optimally.